Trust, Collaboration, and Economic Growth - Kondo, Jiro; Li, Danielle; Papanikolaou, Dimitris (Management Science, 2021)
We propose a macroeconomic model in which variation in the level of trust leads to higher innovation, investment, and productivity growth. The key feature in the model is a hold-up friction in the creation of new capital. Innovators generate ideas but are inefficient at implementing them into productive capital on their own. Firms can help innovators implement their ideas efficiently but cannot ex ante commit to compensating them appropriately. Rather, firms are disciplined only by the value of their reputations—the present value of their future partnerships. We model trust as a public signal and construct a correlated equilibrium. When trust is high, firms anticipate fruitful collaborations and thus can credibly commit to not expropriating inventors, leading to the more efficient production of new capital. Our model can be used to qualitatively replicate the empirical relation between measures of trust and investment, innovation, and productivity growth—at both the micro and macro level. This paper was accepted by Tomasz Piskorski, finance.